Entropy generation through hexagonal cross-sectional duct for constant wall temperature in laminar flow - Öztop, Hakan Fehmi; Sahin, AZ; Dagtekin, I (Wiley, 2004)
Second law analysis of heat transfer in laminar flow for hexagonal cross-section duct was analysed analytically. Geometrical effect of hexagonal duct was considered. The variation of total entropy generation was studied along the duct length. As a working fluid water and unused engine oil were used to compare the effect of fluid in the duct. Results were compared with circular cross-section duct. It is found that the non-dimensional entropy generation in a hexagonal cross-section duct can be as high as a factor of four than that for a circular duct. Further, the unused engine oil gives up to about ten times lower non-dimensional entropy generation values than that of water but needs about ten times more pumping power to heat transfer ratio. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: entropy generation; second law analysis; hexagonal duct; pumping power; laminar flow